The effect of sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB) on the properties of ZnO synthesized by hydrothermal method - Ramimoghadam, Donya; Hussein, Mohd Zobir; Yap, Taufiq Yun Hin (MDPI, 2012)
ZnO nanostructures were synthesized by hydrothermal method using different molar ratios of cetyltrimethylammonium bromide (CTAB) and Sodium dodecyl sulfate (SDS) as structure directing agents. The effect of surfactants on the morphology of the ZnO crystals was investigated by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) techniques. The results indicate that the mixture of cationic-anionic surfactants can significantly modify the shape and size of ZnO particles. Various structures such as flakes, sheets, rods, spheres, flowers and triangular-like particles sized from micro to nano were obtained. In order to examine the possible changes in other properties of ZnO, characterizations like powder X-ray diffraction (PXRD), thermogravimetric and differential thermogravimetric analysis (TGA-DTG), FTIR, surface area and porosity and UV-visible spectroscopy analysis were also studied and discussed.